Application of Powtoon Learning Media to Improve Student Learning Outcomes in Social Studies Grade IV Subjects - Nurpajriah, Siti; Fahri, Muhammad; Rosidah, Noneng Siti (Global Education Journal, 2025)
Social Science subjects are very important to equip students to understand human interaction with their environment. This study aims to improve student learning outcomes in grade IV social studies subjects at Al Giva Nature School Bogor using powtoon learning media. The method of this research is Classroom Action Research with the Kurt Lewin model. The results of the study show that there is an increase in student learning outcomes in social studies subjects in grade IV at the Al Giva Nature School Bogor, which can be seen from the percentage of student completeness. In the pre-cycle student completeness was 45%, in the first cycle the student completeness reached 72.5%, in the second cycle it increased to 75%. In addition, the results of observation of student activities have also increased in each aspect from 84% in the first cycle to 94% in the second cycle. Thus, it can be concluded that the application of powtoon learning media can improve student learning outcomes in grade IV social studies subjects at Al Giva nature school Bogor.